A new circulation index for the detection of monsoon intensity. (9th October 2019) - Wilson, Shinu Sheela; Mohanakumar, Kesavapillai
Abstract: The Asian summer monsoon is characterized by the presence of a low‐level westerly jet stream (LLJ) in the lower troposphere and a tropical easterly jet stream (TEJ) in the upper troposphere. It is interesting to develop an index based on the vertical zonal wind shear and associated rainfall intensity over a monsoon region. The conventional method used to estimate wind shear takes the difference in wind speed between the zonal winds at 850 and 200 hPa. These two fixed levels do not represent the maximum wind speeds at these altitudes and therefore fail to obtain the maximum vertical wind shear. In this study, we propose a new index (the Shinu Mohan [SM] index) by defining the vertical zonal wind shear between the core heights of the low‐level jet stream in the lower troposphere and the TEJ in the upper troposphere, which represents the maximum zonal wind shear in a vertical column of the atmosphere over the summer monsoon region. The core heights of the LLJ and TEJ vary depending on the terrain and the strength of the monsoon circulation. The SM index provides precise vertical shear at each grid point and represents better spatial variability under different terrain conditions. Vertical shear plays a major role in convection and the production of rainfall over a region. Vertical wind shear during extreme monsoon events and the active and break spells of monsoons were analysed by using the SM index and conventional indices. It is interesting to note that the newly defined SM index gives a much better representation of the monsoon intensity compared to conventional indices. Abstract : Climatology of vertical wind shear calculated from (a) core heights of LLJ and TEJ and (b) 850 and 200 hPa for the period 1979–2015.